Oral microbiota and systemic disease - Patrycja Łanowy; Miłosz Bichalski; Joanna Komasa; Katarzyna Mocny-Pachońska; Marta Tanasiewicz (Kazimierz Wielki University, 2019)
The oral cavity is has been resided by thousands of species of microorganisms, which remaining in different relationships. Disturbing the balance between microorganisms and host immunity can lead to the development of many serious local conditions, as well as changes in the organs placed away from the head and neck region. This article describes serious complications of local oral cavity infections like - exacerbation of chronic obstructive pulmonary, brain abscesses, infective endocarditis, diabetes mellitus, and even sepsis. The article also shows the potential connections between periodontal tissue inflammation and neurodegenerative disorders or cancer placed in distant organs. During treatment of periodontal patients, the physician should remember about the influence and risk of bacterial oral diseases.